From the Popularization of Mandarin to Talk About the Inheritance of Dialect -To Take Maanshan as an Example (Asian Journal of Social Science Studies, 2022)
Maanshan, abbreviated as "Ma city", is located in the east of Anhui. It is the intersection of Jiangsu and Anhui, and is also the core of Hefei metropolitan area and Nanjing metropolitan area. With the rapid development of urbanization in China and the popularization of Mandarin, the collision between dialect and Mandarin is more extensive. They interact, influence and connect with each other, forming a unique scenic. This article is based on the contact between Maanshan dialect and Mandarin, to understand the phenomenon and characteristics of the collision between Maanshan dialect and Mandarin in the process of urbanization, and how to make Mandarin coexist harmoniously with dialects, and how to promote Mandarin better while respecting dialects.